Respuesta :

Answer:

x = - 2, x = - [tex]\frac{3}{2}[/tex]

Step-by-step explanation:

Given

f(x) = (- x - 2)(- 2x - 3)

To find the zeros equate f(x) to zero, that is

(- x - 2)(- 2x - 3) = 0

Equate each factor to zero and solve for x

- x - 2 = 0 ( add 2 to both sides )

- x = 2 ( multiply both sides by - 1 )

x = - 2

- 2x - 3 = 0 ( add 3 to both sides )

- 2x = 3 ( divide both sides by - 2 )

x = - [tex]\frac{3}{2}[/tex]

Thus

smaller x = - 2

larger x = - [tex]\frac{3}{2}[/tex]

ACCESS MORE